Construction Safety and Health Factors at the Industry Level: The Case of Singapore - Y.J., Charles Cheah (Penerbit Universiti Sains Malaysia, 2007)
The construction industry is one of the most hazardous industries due to the unique nature of its products and the processes involved. Recent occurrences of highly publicized construction site accidents in Singapore have highlighted the immediate need for the local industry to address safety and health (S&H) hazards. In the past, S&H were considered as isolated aspects on site, but today they have emerged as systemic issues that warrant serious attention at the industry level. The objective of this paper is to examine issues and critical factors affecting S&H standards in Singapore. Clearly, collective efforts should be pursued at the industry level as the country moves towards the ultimate safety management strategy of self-regulation. The findings also indicate that the challenge of making worksites safe should not be placed solely on the contractors, but should be shared by all parties affecting the value chain of construction, including the developers, the consultants and the government. The factors identified through factor analysis may inform legislators and industry practitioners in terms of the sources of problems and help develop effective strategies for improvement. Some of the experiences mentioned in the paper could also be relevant to other countries facing similar circumstances.